1968
DOI: 10.1192/bjp.114.511.749
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Suicide in Depressed In-Patients

Abstract: The assessment of suicidal intent is one of the most important problems of clinical psychiatry. An earlier study (Robin, Brooke and Freeman-Browne, 1968) has confirmed the high incidence of suicide in admissions diagnosed at first contact as suffering from affective disorders, and found that 8 per cent. male in-patients and 5 per cent. female in-patients so diagnosed committed suicide during a follow-up of 6–11 years. It was also shown that in male patient suicides unemployment at the time of first admission a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Several studies of suicide among psychiatric patients using control groups of non-suicides (Pokorny, 1960;Farberow & McEvoy, 1966;Wilson, 1968;Robin et al 1968;Flood & Seager, 1968;McDowall et al 1968;Sletton et al 1972;Myers & Neal, 1978;Barraclough & Pallis, 1975) have been limited to depressed patients and/or included instances of suicide which occurred 11 months or more after discharge from psychiatric care. However, 4 controlled studies of suicide among current general psychiatric patients are available: a study of 71 suicides in a state mental hospital in California, compared with 71 matched control patients who had not killed themselves (Beisser & Blanchette, 1961); 218 psychiatric patients who committed suicide while on the rolls of Veterans Administration hospitals in the United States, compared with 220 other patients who had not committed suicide ; a study of suicide in Denver, Colorado, based on 17 matched pairs of current psychiatric patients (Dean et al 1967); and, finally, all but 2 of 90 suicides compared with 90 control patients seen at the Clarke Institute, Toronto, in psychiatric contact at the time of suicide (Roy, 1982).…”
Section: Controlled Studiesmentioning
confidence: 99%
“…Several studies of suicide among psychiatric patients using control groups of non-suicides (Pokorny, 1960;Farberow & McEvoy, 1966;Wilson, 1968;Robin et al 1968;Flood & Seager, 1968;McDowall et al 1968;Sletton et al 1972;Myers & Neal, 1978;Barraclough & Pallis, 1975) have been limited to depressed patients and/or included instances of suicide which occurred 11 months or more after discharge from psychiatric care. However, 4 controlled studies of suicide among current general psychiatric patients are available: a study of 71 suicides in a state mental hospital in California, compared with 71 matched control patients who had not killed themselves (Beisser & Blanchette, 1961); 218 psychiatric patients who committed suicide while on the rolls of Veterans Administration hospitals in the United States, compared with 220 other patients who had not committed suicide ; a study of suicide in Denver, Colorado, based on 17 matched pairs of current psychiatric patients (Dean et al 1967); and, finally, all but 2 of 90 suicides compared with 90 control patients seen at the Clarke Institute, Toronto, in psychiatric contact at the time of suicide (Roy, 1982).…”
Section: Controlled Studiesmentioning
confidence: 99%
“…Only a handful of studies that used a reasonably exclusive definition of primary depression and a nonsuicidal depressive control group have examined cases who completed suicide or made serious attempts (Asberg, Traskman, & Thoren, 1976;Barraclough & Pallis, 1975;Bunney, Fawcett, Davis, & Gifford, 1969;Farberow & McEvoy, 1966;Flood & Seager, 1968;McDowall, Brooke, Freeman-Browne, & Robin, 1968). With the exception of two studies that focused on biochemical variables (Asberg et al, 1976;Bunney et al, 1969), most of the studies have suggested that nonclinical variables may be the most important predictors of suicidal risk in depressive disorder.…”
mentioning
confidence: 99%
“…The other study, from an English county mental hospital, compared 37 suicides diagnosed 'depression' on their first admission with 37 controls matched for age, sex, and diagnosis (McDowall et al, 1968). All the suicides studied were inpatients when they died but the comparison used information recorded in the case notes of their first admission which had occurred at unspecified periods before the suicide.…”
mentioning
confidence: 99%